Consensus on the Best Practice Guidelines for Psychomotor Intervention in Preschool Children with Autism Spectrum Disorder - Adriana Frazão; Sofia Santos; Ana Rodrigues; Teresa Brandão; Celeste Simões; Paula Lebre (MDPI AG, 2022)
Psychomotor intervention has been used to promote development by the enhancement of psychomotor and socio-emotional competence. However, studies with high-quality evidence, describing psychomotor-intervention processes and outcomes are scarce. Therefore, we aimed to generate expert consensus regarding psychomotor-intervention guidelines to support psychomotor therapists through the design and implementation of interventions for preschool (3-6 years old) children with autism spectrum disorder (ASD). A formal consensus process was carried out, using modified nominal group (phase I) and Delphi survey (phase II) techniques. We recruited 39 Portuguese experts in psychomotor intervention with preschool children with ASD in phase I. Experts participated in at least one of the five online meetings, discussing themes (e.g., objectives, methods, strategies) concerning psychomotor intervention with preschool children with ASD. A deductive thematic analysis from phase I resulted in 111 statements composing round 1 of the Delphi survey. Thirty-five experts completed round 1, and 23 round 2. The experts reached a consensus (agreement > 75%) on 88 statements, grouped under 16 sections, (e.g., intervention source, general setting, intended facilitation-style), reflecting generic psychomotor-intervention guidelines. Consensus guidelines may be used to support transparent and standard psychomotor interventions, although further studies should be undertaken to determine their efficacy.